2012
DOI: 10.1186/1471-2431-12-170
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in HIV-infected children: severity, types and effect on response to HAART

Abstract: BackgroundHIV and anaemia are major health challenges in Africa. Anaemia in HIV-infected individuals is associated with more rapid disease progression and a poorer prognosis if not addressed appropriately. This study aimed at determining the severity and types of anaemia among HIV infected children and its effect on short term response to antiretroviral therapy (ART).MethodsAt baseline, clinical and haematological parameters of 257 HIV-infected ART-naïve children aged 3 months to 18 years were assessed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
22
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 13 publications
11
22
4
Order By: Relevance
“…Thrombocytopenia was observed in 8.1% of the study patients, which is consistent with the study done in India, 7%, 24 in Uganda 8.3%, 23 and in Jima, Ethiopia, 7.8%. 26 Observation in other studies also identified thrombocytopenia in 10%–30% of HIV-infected patients and increased incidence was found to be associated with the progression of HIV disease.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thrombocytopenia was observed in 8.1% of the study patients, which is consistent with the study done in India, 7%, 24 in Uganda 8.3%, 23 and in Jima, Ethiopia, 7.8%. 26 Observation in other studies also identified thrombocytopenia in 10%–30% of HIV-infected patients and increased incidence was found to be associated with the progression of HIV disease.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of anemia before the initiation of ART in this study was 95 (42.8%). This is similar to the studies done in Brazil, 37.5%, 22 and Uganda 47.8% 23 but lower than the Indian study 65.5%. 24 These differences may be due to differences in study populations, socio-demographic characteristics of the study patients, sample size difference and diagnostic criteria used for anemia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Evidence from other studies also shows anemia at ART initiation associated with increased mortality, disease progression (poor virologic response) and reduced quality of life. [27][28][29] Figure 1 Cumulative probability of first-line ART failure among patients in JUSH between 1st January 2010 and 30th June 2016, Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…In sub-Saharan Africa, microcytic anemia (defined as anemia with MCV < 80 fl) is mainly due to iron deficiency, whereas normocytic anemia (defined as anemia with MCV of 80–100 fl) is usually due to anemia of chronic disease. 3,12,13 Macrocytic anemia (defined as anemia with MCV > 100 fl) may be due to the deficiency of either cobalamin or folate. 14 …”
Section: Introductionmentioning
confidence: 99%